2013
DOI: 10.1136/annrheumdis-2013-204113
|View full text |Cite
|
Sign up to set email alerts
|

The relative risk of aortic aneurysm in patients with giant cell arteritis compared with the general population of the UK

Abstract: ObjectivesTo evaluate the risk of aortic aneurysm in patients with giant cell arteritis (GCA) compared with age-, gender- and location-matched controls.MethodsA UK General Practice Research Database (GPRD) parallel cohort study of 6999 patients with GCA and 41 994 controls, matched on location, age and gender, was carried out. A competing risk model using aortic aneurysm as the primary outcome and non-aortic-aneurysm-related death as the competing risk was used to determine the relative risk (subhazard ratio) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(48 citation statements)
references
References 34 publications
0
47
0
1
Order By: Relevance
“…However, this condition is under-diagnosed, as symptoms are frequently mild, non-specific, and insidious. It is estimated that GCA patients have a 2-fold increased risk of aortic aneurysm 24. Symptoms suggestive of involvement of the coronary, mesenteric, and lower extremity arteries are rare.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…However, this condition is under-diagnosed, as symptoms are frequently mild, non-specific, and insidious. It is estimated that GCA patients have a 2-fold increased risk of aortic aneurysm 24. Symptoms suggestive of involvement of the coronary, mesenteric, and lower extremity arteries are rare.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…GCA, the most frequent form of vasculitis in adults,1 is associated with significant morbidity due to vascular problems. For example, studies have found that GCA is associated with arterial complications like blindness,2 aortic aneurysms,3 myocardial infarction4–6 and ischaemic stroke 6–8. These previous studies have focused on arterial events, with the risk of venous thromboembolism (VTE) events in patients with GCA being largely ignored despite an array of plausible mechanisms 9 10…”
Section: Introductionmentioning
confidence: 99%
“…Patients with GCA have a twofold increased risk of aortic aneurysm, 11 and imaging of the aorta is required in all patients at the time of diagnosis. If the aorta is involved in the inflammatory process, periodic imaging surveillance is mandatory because aortic expansion may occur with the risk of late rupture and dissection 12 …”
Section: Discussionmentioning
confidence: 99%